Libido–sexual disorders and abandonment of injectable contraceptives among users of the Ivorian Association for Family Well-Being in Korhogo, Côte d’Ivoire - Essis, Esme Marie-Laure; Yeo, Katienin Jeanne; Amalaman, Djedou Martin; Konan, Loukou Leandres; Bamba, Iba; Coulibaly, Koné S. Aminata; Kpebo, D. Olga Denise; Orsot, Tetchi; Delafosse, Joseph; Aka, Joseph (Frontiers in Global Women's Health, 2023)
Introduction: The recent introduction of modern contraceptive methods in resource-limited countries is confronted with the occurrence of undesirable effects that hinder their use in the long term. This study of clients of the Ivorian Association for Family Well-Being in Korhogo describes the libido-sexual problems associated with the discontinuation of injectable contraceptives. Materials and methods: A qualitative study collected data from 15 previous users (24 to 38 years old) of the contraceptive injection by intramuscular route with an action duration of 2 to 3 months. Then, 05 health workers aged 35 to 60 years were interviewed individually. Results: Injectable contraceptives were the source of troublesome side effects, particularly libido-sexual disorders, which had an impact on the intimacy of the households and provoked their abandonment or the change of contraceptive method by the users. Conclusion: The libido-sexual problems associated with the use of injectable contraceptives have had a negative impact on the intimacy of couples, creating a crisis of confidence and tensions that have led to the abandonment of the method or a change in the method of contraception. It would be advisable to supervise the use of modern contraceptive methods (MCMs) for medical examinations and analyses, to investigate and manage adverse events related to the use of MCMs, to train health workers on MCMs for a better management of users, to improve communication between health workers and users, and to improve the follow-up of MCM users, especially those presenting adverse events.